Incidence of systemic granulomatosis is modulated by the feeding sequence and type of enrichment in meagre (Argyrosomus regius) larvae. (25th November 2018) - Ruiz García, Miguel Ángel; Hernández‐Cruz, Carmen M.; Caballero, Maria Jose; Fernández‐Palacios, Hipólito; Saleh, Reda; Izquierdo, Marisol; Betancor Quintana, Mónica Beatriz
Abstract: Systemic granulomatosis is the most frequent disease in juvenile and adult meagre, but studies regarding the first appearance of granulomas in larvae do not exist. In order to evaluate this, meagre larvae were fed four different feeding regimes as follows: RS and RO (rotifer enriched with Easy DHA Selco or Ori‐Green from 3 to 30 dph respectively), RAS and RAO (rotifer enriched with Easy DHA Selco or Ori‐Green from 3 to 21 dph and Artemia enriched with Easy DHA Selco or Ori‐Green from 12 to 30 dph respectively). All treatments were also fed with commercial microdiet from 20 to 30 dph. At 30 dph weight, length, specific growth rate and survival were significantly higher in Artemia‐ fed larvae, regardless of the enrichment. Microscopic first appearance of granulomas was observed in 20 dph larvae fed RS and RO. At 30 dph granulomas and thiobarbituric acid reactive substances (TBARS), values were significantly higher in RS and RO‐fed larvae than in RAS and RAO‐fed larvae. The results showed that granulomas first appeared in meagre larvae at 20 dph when fed rotifers only. Conversely, a reduced appearance of granulomas and lipid peroxidation occurs when Artemi a is included in the feeding sequence reinforcing the hypothesis of a nutritional origin of the systemic granulomatosis.